State and Islamic Law: A Study of Legal Politics on Zakat as a Tax Deduction in Aceh - Mahdi Syahbandir; Wais Alqarni; Syahrizal Abbas; Bukhari Ali; Fauzan Samad (AHKAM : Jurnal Ilmu Syariah, 2022)
This study examines zakat (obligatory charity) as a tax deduction in Aceh. Currently, the existing legal rule stipulates that zakat paid by muzakkī (zakat payers) to the National Zakat Board (BAZNAS) and Zakat Official Institution (LAZ) is deducted from taxable income. However, this rule has not been applied since there is no Government Regulation. This empirical legal study used a statutory approach, analyzing the point of view of legal politics theory. This study concludes that the State and Islamic Law in Aceh are closely related to the political context of Indonesian law. The government regulations from the Old Order to the Reform Era related to Islamic Law or Muslims have been greatly influenced by political configurations. When the configuration is democratic, the legal character embraces democratic values and vice versa. As a result, the legal regulations regarding zakat have not yet been enforced due to the strong political configuration. However, referring to the arguments and logic of legal politics that the government is democratic towards the aspirations in Aceh, the Governmental Regulation Draft/Rancangan Peraturan Pemerintah (RPP) for Zakat as Tax Deduction will strengthen the previous legal rule, stipulating zakat as a tax deduction factor. The unification of zakat and taxes in one legal instrument by the government, which has political and structural authority, will be able to realize justice and economic and social welfare of the community as the primary goal of zakat.   AbstrakPenelitian ini bertujuan untuk mengkaji zakat sebagai faktor pengurang pajak di Aceh. Berdasarkan aturan hukum yang ada bahwa zakat yang dibayarkan oleh muzaki kepada BAZNAS atau LAZ dikurangkan dari penghasilan kena pajak. Namun sampai saat ini aturan ini belum teraplikasi karena belum ada Peraturan Pemerintah. Kajian ini merupakan studi hukum empiris dengan menggunakan pendekatan perundang-undangan, dianalisis dari sudut teori politik hukum. Penelitian ini menyimpulkan bahwa hubungan antara agama, negara, dan hukum Islam di Aceh memiliki kaitan yang erat dengan konteks politik hukum Indonesia secara umum. Aturan pemerintah yang terkait dengan hukum Islam atau umat Islam sejak masa orde lama bahkan sampai reformasi dipengaruhi oleh konfigurasi politik, jika konfigurasinya demokratis maka karakter hukumnya juga demokratis begitu juga sebaliknya. Karena itu, aturan hukum tentang zakat tersebut sampai saat ini masih belum dapat diberlakukan karena kuatnya konfigurasi politik. Mengacu pada argumen dan logika politik hukum, pemerintah bersikap demokratis terhadap aspirasi di Aceh dengan membuat Rancangan Peraturan Pemerintah (RPP) tentang Zakat sebagai Pengurangan Pajak yang akan menguatkan aturan hukum sebelumnya, yaitu zakat sebagai faktor pengurang pajak. Penyatuan zakat dan pajak dalam satu instrumen hukum oleh pemerintah yang memiliki kewenangan politik dan struktural akan dapat mewujudkan keadilan dan kesejahteraan ekonomi dan sosial masyarakat sebagai tujuan utama zakat.